Possible Protective Role of Melatonin in Pediatric Infectious Diseases and Neurodevelopmental Pathologies - Molina-Carballo, Antonio; Jerez-Calero, Antonio Emilio; Muñoz-Hoyos, Antonio (Journal of Child Science, 2020)
Melatonin, produced in every cell that possesses mitochondria, acts as an endogenous free radical scavenger, and improves energetic metabolism and immune function, by complex molecular crosstalk with other intracellular compounds. There is greatly increasing evidence regarding beneficial effects of acute and chronic administration of high melatonin doses, in infectious, developmental, and degenerative pathologies, as an endothelial cell and every cell protectant.
Keywords: melatonin; inflammatory disorders; COVID-19; neurodevelopmental pathologies; children